2019
DOI: 10.1590/0103-8478cr20180932
|View full text |Cite
|
Sign up to set email alerts
|

Leaf area estimation of squash ‘Brasileirinha’ by leaf dimensions

Abstract: The objectives of this work were estimate the leaf area of squash ‘Brasileirinha’ by linear dimensions of the leaves and check models available in the literature. An experiment was conducted in the 2015/16 sowing season. Were collected 500 leaves and in each one, were measured the length (L), width (W) and length×width product (LW) and determined the real leaf area (LA). Then, 400 leaves were separated to generate models of the leaf area (LA) as a function of linear dimension (L, W or LW) of squash. The remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
(32 reference statements)
1
16
1
1
Order By: Relevance
“…In this way, note that of the nine equations tested, only the linear first degree and quadratic models generated from the width (W) presented a linear coefficient β statistically equal to zero and angular coefficient ( β ) statistically equal to one. This finding is very important because, according to Toebe et al [28] indicates precision of these models in the estimated leaf area, once the observed leaf area is zero, the values estimated by the equation will also be zero and as 1 cm 2 of the observed leaf area increases, the equation will add 1 cm 2 in the estimated leaf area. However, considering these two equations, the quadratic model presented values of mean absolute error (MAE) and root mean square error (RQME) closest to zero, in addition to the value of the index d closest to the unit, which suggests a more predictive leaf area of Coffea dewevrei by this model.…”
Section: Resultsmentioning
confidence: 95%
“…In this way, note that of the nine equations tested, only the linear first degree and quadratic models generated from the width (W) presented a linear coefficient β statistically equal to zero and angular coefficient ( β ) statistically equal to one. This finding is very important because, according to Toebe et al [28] indicates precision of these models in the estimated leaf area, once the observed leaf area is zero, the values estimated by the equation will also be zero and as 1 cm 2 of the observed leaf area increases, the equation will add 1 cm 2 in the estimated leaf area. However, considering these two equations, the quadratic model presented values of mean absolute error (MAE) and root mean square error (RQME) closest to zero, in addition to the value of the index d closest to the unit, which suggests a more predictive leaf area of Coffea dewevrei by this model.…”
Section: Resultsmentioning
confidence: 95%
“…using leaf dimensions as and power were adjusted for the estimation of the leaf area of Acacia mangium Willd. According to Toebe et al [11], these three models are reliable, presenting high predictive efficiency and high reliability, being used with precision in the estimation of leaf area of several crops, without the necessity of the destruction of the leaves. Corroborating this assertion, several authors have tested and adjusted these models for other species, such as Crotalaria juncea [8], Litchi chinensis Sonn.…”
Section: Ssionmentioning
confidence: 99%
“…Corroborating this assertion, several authors have tested and adjusted these models for other species, such as Crotalaria juncea [8], Litchi chinensis Sonn. [9], Artocarpus heterophyllus [10], Cucurbita moschata [11], Pennisetumglaucum [12] and Plectranthus barbatus Andrews [13]. Table 3 describes the nine models of equations generated for the estimation of the leaf area of Acacia mangium Willd.…”
Section: Ssionmentioning
confidence: 99%
See 1 more Smart Citation
“…A superfície da folha apresenta-se essencialmente plana e achatada, o que facilita, consideravelmente, o aumento da relação superfície/volume, permitindo assim, a realização das trocas gasosas (ALMEIDA; ALMEIDA, 2018). Ressalta-se que a área foliar é frequentemente utilizada para medir o crescimento das plantas, estando diretamente relacionada à fotossíntese e taxa de transpiração, entre outros processos fisiológicos (TOEBE et al, 2019).…”
Section: Introductionunclassified